Physician Self-Referral and Imaging Use Appropriateness: Negative Cervical Spine MRI Frequency as an Assessment Metric - Amrhein, T.J.; Paxton, B.E.; Lungren, M.P.; Befera, N.T.; Collins, H.R.; Yurko, C.; Eastwood, J.D.; Kilani, R.K. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Imaging self-referral is increasingly cited as a contributor to diagnostic imaging overuse. The purpose of this study was to determine whether ownership of MR imaging equipment by ordering physicians influences the frequency of negative cervical spine MR imaging findings. MATERIALS AND METHODS: A retrospective review was performed of 500 consecutive cervical spine MRIs ordered by 2 separate referring-physician groups serving the same geographic community. The first group owned the scanners used and received technical fees for their use, while the second group did not. Final reports were reviewed, and for each group, the percentage of negative study findings and the frequency of abnormalities were calculated. The number of concomitant shoulder MRIs was recorded. RESULTS: Five hundred MRIs meeting inclusion criteria were reviewed (250 with financial interest, 250 with no financial interest). Three hundred fifty-two had negative findings (190 with financial interest, 162 with no financial interest); there were 17.3% more scans with negative findings in the financial interest group (P = .006). Among scans with positive findings, there was no significant difference in the mean number of lesions per scan, controlled for age (1.90 with financial interest, 2.19 with no financial interest; P = .23). Patients in the financial interest group were more likely to undergo concomitant shoulder MR imaging (24 with financial interest, 11 with no financial interest; P = .02). CONCLUSIONS: Cervical spine MRIs referred by physicians with a financial interest in the imaging equipment used were significantly more likely to have negative findings. There was otherwise a highly similar distribution and severity of disease between the 2 patient samples. Patients in the financial interest group were more likely to undergo concomitant shoulder MR imaging. FIfinancial interestNFIno financial interestOEDSorder entry decision support